Approaching the Lithiation Limit of MoS2 While Maintaining Its Layered Crystalline Structure to Improve Lithium Storage. Issue 11 (20th February 2019) - Zhu, Zhiqiang; Tang, Yuxin; Leow, Wan Ru; Xia, Huarong; Lv, Zhisheng; Wei, Jiaqi; Ge, Xiang; Cao, Shengkai; Zhang, Yanyan; Zhang, Wei; Zhang, Hongwei; Xi, Shibo; et al.
Abstract: MoS2 holds great promise as high‐rate electrode for lithium‐ion batteries since its large interlayer can allow fast lithium diffusion in 3.0–1.0 V. However, the low theoretical capacity (167 mAh g −1 ) limits its wide application. Here, by fine tuning the lithiation depth of MoS2, we demonstrate that its parent layered structure can be preserved with expanded interlayers while cycling in 3.0–0.6 V. The deeper lithiation and maintained crystalline structure endows commercially micrometer‐sized MoS2 with a capacity of 232 mAh g −1 at 0.05 A g −1 and circa 92 % capacity retention after 1000 cycles at 1.0 A g −1 . Moreover, the enlarged interlayers enable MoS2 to release a capacity of 165 mAh g −1 at 5.0 A g −1, which is double the capacity obtained under 3.0–1.0 V at the same rate. Our strategy of controlling the lithiation depth of MoS2 to avoid fracture ushers in new possibilities to enhance the lithium storage of layered transition‐metal dichalcogenides. Abstract : By fine‐tuning the lithiation depth of MoS2, the layered crystalline structure can be well preserved when cycled (3.0–0.6 V vs. Li + /Li), which is accompanied with the expansion of the interlayer distance. These features enable the stable cycling of commercial μm‐sized MoS2 with higher capacity and faster rate capability, making it a promising anode for fast‐charging lithium ion batteries.